Sinkholes and the Engineering and Environmental Impacts of Karst: Proceedings of the Fourteenth Multidisciplinary Conference 2015
DOI: 10.5038/9780991000951.1026
|View full text |Cite
|
Sign up to set email alerts
|

Conduit Flow in the Cambrian Lone Rock Formation, Southeast Minnesota, U.S.A.

Abstract: dominated units generally have bedding-parallel and vertically oriented apertures less than a few centimeters. The process by which the bedding-parallel secondary pore networks form remains obscure; some appear to be mechanically developed. However, interstitial carbonate cement within these units leads to the possibility of dissolution being a minor factor in the formation's groundwater flow characteristics. These dye traces were conducted at three different sites across a twenty-three kilometer distance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The Lone Rock is mostly composed of a fine-grained sandstone and siltstone with interbedded shale and dolostone (Mossler, 2008). Dye traces from St. Lawrence stream sinks at three sites in southeast Minnesota have been detected at Lone Rock springs (Barry et al, 2015). These traces have demonstrated that the Lone Rock also has a karstlike conduit flow component.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The Lone Rock is mostly composed of a fine-grained sandstone and siltstone with interbedded shale and dolostone (Mossler, 2008). Dye traces from St. Lawrence stream sinks at three sites in southeast Minnesota have been detected at Lone Rock springs (Barry et al, 2015). These traces have demonstrated that the Lone Rock also has a karstlike conduit flow component.…”
Section: Discussionmentioning
confidence: 92%
“…These traces have demonstrated that the Lone Rock also has a karstlike conduit flow component. Observed breakthrough travel velocities were between 21-214 meters/day using passive charcoal detectors and 314 meters/day using automatic water samplers; dye was still being detected over one year later at springs monitored from one of the tracing sites (Barry et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The results of tracer tests in the Březová nad Svitavou spring area clearly showed that the fracture-controlled conduits did not form only short, isolated segments, but an extensive interconnected network through which 1100 L/s flows at a velocity of 400-650 m/day over a distance of several kilometers to the largest springs in the BCB, which now supply the second largest city in the Czech Republic with groundwater [21]. Comparable flow velocities have been found in open fractures in siliciclastic-carbonate rocks in Minnesota and Wisconsin, USA (35-750 m/day [8,9]), in conduits in Sherwood sandstone with intergranular carbonate cement in the UK [34], and in fissures in sandstone with carbonate beds in Luxembourg (2-8400 m/day [35]).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogeological characteristics and karst evolution have been described in numerous publications in both fractured and/or folded telogenetic and young eogenetic highpercentage carbonates [3]. Less information is available on karst in evaporites [4], quartzites [5], and especially for lithologies at the transition between carbonates and siliciclastics [6][7][8][9][10]. Ghost-rock karst is a specific type of karstification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation